Marketing experiencial y su influencia en el posicionamiento de marca de Bryam Ulloa - fotografía, Trujillo 2021 - Ulloa Paredes, Bryam Efrén (2021)
The general objective of this research is to determine the influence of experiential marketing in improving the brand positioning of Bryam Ulloa Photography, Trujillo 2021. The problem formulated was: How does experiential marketing influence the brand positioning of Bryam Ulloa Photography, Trujillo 2021? and it was raised as a hypothesis: Experiential marketing will positively influence the brand positioning of Bryam Ulloa - Photography, Trujillo 2021. Likewise, there was a population of 290 clients of Bryam Ulloa - Photography from January to August 2021; and, consequently, a sample of 165 clients. The research design used was non-experimental descriptive - cross-sectional because it aimed to describe the current reality as a diagnosis at a given time. As for the techniques, the survey was used and the questionnaire as instruments. Likewise, the conclusion reached was that experiential marketing and brand positioning have a considerable positive relationship. In other words, the experiential marketing indicators of Bryam Ulloa - Photography are defined as strengths, causing the level of brand positioning to be high.